HEATWAVES AND HEALTHCARE: BRIDGING DATA AND FRONTLINE PRACTICE - Tonnelier, Margo (Srpski medicinski časopis Lekarske komore, 2025)
Heatwaves and related environmental events expose critical vulnerabilities in overburdened health systems and underscore the need to integrate clinical and environmental data to support timely public health interventions. However, healthcare professionals’ participation in data collection is often limited by high workloads and fragmented, restrictive health information system architectures. This article explores strategies to strengthen the link between public health data production and clinical response to mitigate the health risks associated with heatwave events. Field immersion programs for epidemiologists enhance understanding of operational constraints and promote the design of pragmatic interventions. However, the lack of standardized health measures and a widely accepted conceptual framework limits the effectiveness of heatwave epidemiology. We argue that such approaches can systematically improve the validity, applicability, and equity of public health research and practice, and propose a framework for standardized health monitoring during heatwaves.
Keywords: heatwaves; epidemiology; public health; health risks